(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What motivates a person to unleash his creativity and which are inhibitory factors that inhibit creativity? Purpose: The purpose of the article is to show motivational and inhibiting factors that influence human creativity. Method: Using the qualitative method, the method of encoding and selecting the relevant codes by which relations can be shown, we show relationships between positive and inhibiting factors for human creativity. Results: The results of the research have shown that there are many different motivational factors that influence human creativity. Organization: The organization’s management has received a response to the creative climate in organizations it is not something we take for granted but requires a systematic approach to providing creative climate. Society: The research shows that the wider environment also has an impact in creating a creative climate. Originality: The originality of the research is that it is necessary to create a creative atmosphere deliberately and very carefully nurtured. Limitations/Future Research: In the study, we confined ourselves to the positive and inhibiting factors that were found in the literature. For a wider overview of the factors, additional literature should be studied and the impact of individual motivation factors on human creativity should be explored.